'Where are they now'? A survey of former oral surgery trainees. (14th July 2020) - Gormley, M.; Ali, S.; French, K.; Wilson, G.; Stagnell, S.; Bailey, E.
Abstract: Introduction: This study aimed to gather demographic data from the oral surgery workforce who have experienced a formal training pathway, their current roles, commitments, competencies and how they believe oral surgery training could be improved. Methods: A 22‐question online survey was developed and distributed to 70 former oral surgery trainees. Trainee details were retrospectively obtained using the British Association of Oral Surgeons (BAOS) Consultants and Senior Trainers (CAST) group mailing list and the oral surgery trainee mailing list and potential participants were invited via email. Results: Six participants reported not having had formal training and were excluded, resulting in a 47% response rate. The majority (78%) of former oral surgery trainees appear to spend most of their working week in hospital practice, with 63% in oral surgery consultant or honorary consultant positions. Participants reported a mean average of five WTE oral surgery sessions working for the NHS and one WTE private session. Oral surgeons have a broad remit of roles and responsibilities including teaching and training, policy making, research, leadership and management. Respondents suggested improvements for any future oral surgery specialty curriculum, including more leadership and management training to ensure trainees are well prepared for senior posts. Conclusion: Overall, this survey demonstrates the broad and diverse skills of the oral surgery workforce. The majority of former oral surgery trainees currently hold consultant level positions and are mainly based in hospital practice. This study also demonstrated that a large proportion of the oral surgery workforce commitment is to the public sector and education.